(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2025)
The results of an Action-Research experience promoted by the Regional School Office for Lombardy between the school and the services of the penal and precautionary enforcement of liberty for the realisation of innovative paths of education to legality will be presented. We will illustrate how two classes of adult students, outside and inside prison, have experimented - through literature, co-planning, university involvement, participatory methodologies - an effective model of education to legality as a form of active citizenship.